2017
DOI: 10.1364/boe.8.005518
|View full text |Cite
|
Sign up to set email alerts
|

Analytical models for time-domain diffuse correlation spectroscopy for multi-layer and heterogeneous turbid media

Abstract: Abstract:A novel approach for time-domain diffuse correlation spectroscopy (TD-DCS) has been recently proposed, which has the unique advantage by simultaneous measurements of optical and dynamical properties in a scattering medium. In this study, analytical models for calculating the time-resolved electric-field autocorrelation function is presented for a multilayer turbid sample, as well as a semi-infinite medium embedded with a small dynamic heterogeneity. To verify the analytical models, we used Monte Carlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Recently, an implementation and theory for time-domain DCS (TD-DCS), or pathlength-resolved DCS, has been developed, aiming at improving the depth sensitivity by discriminating short and long photon pathlengths. [10][11][12] By employing a pulsed laser with a certain coherence length, Sutin et al 10 simultaneously measured the time-of-flight of photons and DCS speckle fluctuations and demonstrated that TD-DCS was able to separate the contribution of photons from shallow and deep layers. Very recently this technique has also been successfully applied to in vivo measurements on human tissues including adult head.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an implementation and theory for time-domain DCS (TD-DCS), or pathlength-resolved DCS, has been developed, aiming at improving the depth sensitivity by discriminating short and long photon pathlengths. [10][11][12] By employing a pulsed laser with a certain coherence length, Sutin et al 10 simultaneously measured the time-of-flight of photons and DCS speckle fluctuations and demonstrated that TD-DCS was able to separate the contribution of photons from shallow and deep layers. Very recently this technique has also been successfully applied to in vivo measurements on human tissues including adult head.…”
Section: Introductionmentioning
confidence: 99%
“…11 At the same time, TD-DCS analytical theory for multilayer and heterogeneous turbid media was also presented. 12 The photon detection of TD-DCS is very similar to time-resolved spectroscopy (TRS) system, except for the detection fibers. TD-DCS uses single mode fiber to ensure detection of light from a single speckle (or a single coherence area).…”
Section: Introductionmentioning
confidence: 99%
“…Our approach differs from previous theoretical works. Recently, Li et al introduced an analytical model for TD-DCS applied to multi-layer heterogeneous turbid samples 26 . In their approach is represented as a product of several negative exponential functions: …”
Section: Introductionmentioning
confidence: 99%
“…In other words, TD-DCS can provide higher sensitivity detection for deep dynamics. In recent years, TD-DCS technology has developed rapidly, including the proposal of various theoretical models, the verification of simulation and phantom experiments, as well as in vivo measurement of the human arm and head [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%